1999
DOI: 10.1021/jp992353u
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Polymerization of Formaldehyde on Cu(100)

Abstract: The adsorption of formaldehyde (H2CO) on clean Cu(100) at 85 K has been studied using electron energy loss spectroscopy (EELS), X-ray photoelectron spectroscopy (XPS), and temperature-programmed desorption (TPD). For coverages up to (1.06 ± 0.22) × 1015 H2CO molecules/cm2, formaldehyde spontaneously polymerized to form a monolayer of disordered poly(oxymethylene) (POM), arranged with the chain directions parallel to the surface plane. Thermal decomposition/desorption of the polymer monolayer occurred by three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 47 publications
6
37
1
Order By: Relevance
“…The polymerization of H 2 CO is also observed on clean surfaces of Cu(110), 3,11 Ni(110), 9 Pd(111), 6 Pt(111), 4 and Zn(0001). 11 It has also been suggested that a methoxy intermediate is formed on Ni(110) 9 and Fe(100) 10 surfaces together with adsorbed CO and hydrogen. Oxygenation depresses the reactivity of Ru(001) for dehydrogenation of H 2 CO. 8 Reaction of H 2 CO with preadsorbed oxygen on Rh(111) forms CO, paraformaldehyde, formate, and η 1 -formaldehyde.…”
Section: Introductionmentioning
confidence: 89%
“…The polymerization of H 2 CO is also observed on clean surfaces of Cu(110), 3,11 Ni(110), 9 Pd(111), 6 Pt(111), 4 and Zn(0001). 11 It has also been suggested that a methoxy intermediate is formed on Ni(110) 9 and Fe(100) 10 surfaces together with adsorbed CO and hydrogen. Oxygenation depresses the reactivity of Ru(001) for dehydrogenation of H 2 CO. 8 Reaction of H 2 CO with preadsorbed oxygen on Rh(111) forms CO, paraformaldehyde, formate, and η 1 -formaldehyde.…”
Section: Introductionmentioning
confidence: 89%
“…The conclusion is that coupling of formaldehyde adsorbates through their carbon ends takes precedent over any C-O bond-scission or dehydrogenation steps on the vanadium surface. The most common thermal chemistry seen for formaldehyde on transition metal surfaces has been its decomposition to carbon monoxide and hydrogen [15,72,75,[85][86][87][88][89][90][91], but diolate formation as reported here is known in homogeneous catalysis with titanium [92] and vanadium [93,94] low-valent compounds, and has also been reported on the surfaces of titanium [95] and uranium [96] oxides. The only other precedent for diolate formation on a metal is that reported on Mo(110) [86], another early transition metal.…”
Section: Surface Chemistry Of Formaldehyde and Methanolmentioning
confidence: 58%
“…Surface reactions of HSCH 2 CH 2 OH Fig. 1 shows the temperature-programmed reaction/desorption spectra of 1.5 L HSCH 2 CH 2 OH adsorbed on Cu(1 0 0) at 115 K, collected for the ions of 15,16,26,27,42,43, and 60 amu, representative of desorption of CH 4 , C 2 H 4 , CH 3 CHO, and HSCH 2 CH 2 OH. No HSCH 2 CH 2 OH molecular desorption, as shown in the 60 amu trace, is observed at 1.5 L exposure.…”
Section: Resultsmentioning
confidence: 99%
“…In the thermal decomposition of CH 3 OH on Cu(1 0 0), CH 3 Odecomposes to evolve CH 2 O between 370 and 450 K, however, -CH 2 O-surface intermediate is not detected by high-resolution electron energyloss spectroscopy (HREELS) [4]. Interaction between CH 2 O and Cu(1 0 0) has been investigated [15]. Upon CH 2 O adsorption on Cu(1 0 0) at 85 K, the molecules polymerize, forming poly (oxymethylene).…”
Section: Vibrational Studies Of Thermal Decomposition Of Hsch 2 Ch 2 Ohmentioning
confidence: 99%